Media Sosial dan Revolusi Politik: Memahami Kembali Fenomena “Arab Spring” dalam Perspektif Ruang Publik Transnasional - Ahmad. R Mardhatillah Umar; Arief Bakhtiar Darmawan; Faela Sufa Sufa; Gebyar Lintang Ndadari (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This paper aims to analyze some linkages between revolution, public sphere, and transnational activism through social media in the Middle East. A revolution in Tunisia in 2011 became an international issue aft er the revolution spreaded to other states in the region. Aft er Tunisia, protest movements began to ignite in Egypt, Libya, Yemen, and Jordania. This wave of revolution comes into a public discourse: what causes this movement? How could a revolution in one country inspire another revolution in another country? To answer these questions, we analyze the role of social media as a “bridge” to connect activists in the Middle East to make a revolution. We conclude that transnational activism was formed by routine and massive reports from media which explained what hadhappened in the Middle East during the revolution. The reports were followed by a spread of the idea of democracy and civil rights through social media. As a consequence, revolution took place in several othercountries whose socio-cultural tradition are similar to that of Tunisia.